12 iconic American monuments and symbols - Koestler-Grack, Rachel A., 1973- (Iconic America, 2025)
"Middle-grade readers will gain an understanding about the importance of 12 iconic monuments and symbols in America. Stat boxes, sidebars, and "Think About It" features support critical thinking skills and reading comprehension"--